2009
DOI: 10.2147/tcrm.s3462
|View full text |Cite
|
Sign up to set email alerts
|

A review of the applications of the hydrofiber dressing with silver (Aquacel Ag®) in wound care

Abstract: Aquacel Ag® (ConvaTec, Princeton, NJ, USA) is a new hydrofiber wound dressing consisting of soft non-woven sodium carboxymethylcellulose fibers integrated with ionic silver. It is a moisture-retention dressing, which forms a gel on contact with wound fluid and has antimicrobial properties of ionic silver. We present a current literature review on Aquacel Ag®, of both in vitro and in vivo efficacy and clinical applications. In vitro and in vivo studies have demonstrated the wide antimicrobial properties of Aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 34 publications
1
64
0
4
Order By: Relevance
“…Based on the MTT data one could expect approximately 100% cell death, which was supported by light microscope pictures. This is also supported by previous work showing that silver ions are toxic to skin cells in vitro (Barnea, Weiss & Gur, 2010;Burd et al, 2007; Paddle- Ledinek, Nasa & Cleland, 2006;Poon & Burd, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…Based on the MTT data one could expect approximately 100% cell death, which was supported by light microscope pictures. This is also supported by previous work showing that silver ions are toxic to skin cells in vitro (Barnea, Weiss & Gur, 2010;Burd et al, 2007; Paddle- Ledinek, Nasa & Cleland, 2006;Poon & Burd, 2004).…”
Section: Discussionsupporting
confidence: 87%
“…This was reflected in other studies that demonstrated difficulty in joint mobility with the hardening of dressing over the joints. [6,9] In particular, the use of SSD achieved greater flexibility and ROM when compared to AQUACEL ® Ag for burn wounds. [9] Caruso et al [14] found the flexibility excellent to very good in the 82% of patients with 19% reporting average to poor flexibility.…”
Section: Flexibility and Range Of Movementmentioning
confidence: 99%
“…[4] AQUACEL ® Ag (ConvaTec, Skillman, NJ, USA) is a soft nonwoven sodium carboxymethylcellulose fiber that forms a gel and has the capacity to absorb exudate and contour to the wound bed. [4,9] Currently, there are only a few clinical studies within the peer-reviewed literature that investigate the use of the AQUACEL ® Ag BURN glove. [3,10] …”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used was chlorhexidine acetate 0.5% (Bactigrass ®), novel silver containing hydrofiber (Aquacell Aq ®), polyhexanide containing biocellulose dressing (Suprasorb ®) and polyurethane film (Omniderm ®). These burn dressing have been shown effective in superficial partial thickness and deep partial thickness (second degree) burn injuries (31)(32)(33)(34).…”
Section: Table 1 Patient Distribution and Mean Ages According To Thementioning
confidence: 99%